Use and results of astegolimab in the management of severe asthma: what is known? - Lozada Martínez , Ivan David (2023)
Asthma is a chronic inflammatory disease of the respiratory tract which causes high health costs, substantially affects the quality of life and, depending on certain associated risk factors, reduces the functional capacity of the sufferer. By 2019, asthma affected 262 million people (4.3 % of the world’s population) and caused 461,000 deaths. It is estimated that therewill be an additional 100 million people with asthma by 2025. Severe asthma is a phenotype resistant to corticosteroids which causes a greater number of exacerbations and substantially affects the quality of life and functional capacity of the affected person. Its management was initially aimed at suppressing the symptoms and then evolved to understand, although not completely, the intrinsic systems of its generation. Thus, new ways of influencing its management have been studied by modulating the immune response and the inflammatory cascade with the generation of biological drugs. As a result of the study and identification of various endotypes and phenotypes, drugs with different mechanisms of action have been designed and have demonstrated to be considerably useful in recent years. However, there is evidence that resistance even to these drugs has occurred, being necessary to continue researching new therapeutic targets. Astegolimab is a novel human IgG2 monoclonal antibody that blocks IL-33 signaling by targeting ST2, its receptor, thus controlling the inflammatory response in severe asthma. A phase 2b clinical trial is currently undergoing, although previous results have found positive and significant results regarding immunomodulation, pulmonary function, symptomatology and quality of life. At present, there is almost no literature that has analyzed the potential of astegolimab in severe asthma, and practically only trials that have evaluated it and some reviews that have shared its pharmacokinetics and pharmacodynamics are available. Based on the above, the aim of this review is to synthesize evidence related to the results of the use of astegolimab insevere asthma and discuss epidemiological and pathophysiological aspects that highlight the need for the development of a safe, effective and efficient drug.